2020
DOI: 10.3390/toxins12030143
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Yeast Alleviates Ochratoxin A-Induced Hepatotoxicity via Modulation of the PI3K/AKT and Nrf2/Keap1 Signaling Pathways in Chickens

Abstract: The aim of this study was to investigate the protective effects of selenium yeast (Se-Y) against hepatotoxicity induced by ochratoxin A (OTA). The OTA-induced liver injury model was established in chickens by daily oral gavage of 50 µg/kg OTA for 21 days. Serum biochemistry analysis, antioxidant analysis, as well as the qRT-PCR and Western blot (WB) analyses were then used to evaluate oxidative damage and apoptosis in chicken liver tissue. The results showed that Se-Y significantly increased liver coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…A recent study revealed that AFB 1 -induced liver damage in broiler chicks has been associated with dysregulating the Nrf2 signaling pathway [ 13 ]. Therefore, Nrf2 signaling is regarded as the most significant therapeutic target for preventing and treating oxidative stress-induced liver damage [ 24 , 25 ]. Although, a study reported that luteolin has a therapeutic impact on ochratoxin A-induced oxidative injury in NRK-52E kidney cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that AFB 1 -induced liver damage in broiler chicks has been associated with dysregulating the Nrf2 signaling pathway [ 13 ]. Therefore, Nrf2 signaling is regarded as the most significant therapeutic target for preventing and treating oxidative stress-induced liver damage [ 24 , 25 ]. Although, a study reported that luteolin has a therapeutic impact on ochratoxin A-induced oxidative injury in NRK-52E kidney cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…OTA contamination in feed seriously affects the health and production performance of animals, which may also harm people through the food chain. Numerous studies have reported that OTA has renal toxicity, liver toxicity, and carcinogenic and teratogenic effects [ 7 , 8 , 9 , 10 ]. In recent years, biodegradation strategies for OTA detoxification have become a promising method.…”
Section: Discussionmentioning
confidence: 99%
“…The target organs of OTA are considered to be the kidney and liver. Studies have reported that OTA causes nephrotoxicity, hepatotoxicity, immunotoxicity, teratogenicity, genotoxicity, and carcinogenicity in animals [ 7 , 8 , 9 , 10 ]. Plenty of animal feeding trials have been performed to evaluate the potential toxicity of OTA.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid luteolin regulates Nrf2 and HIF-1α signalling pathways to alleviate OTA-induced oxidative stress (Liu et al 2020 ). Carotenoid astaxanthin similarly to luteolin protects against OTA-induced kidney injury (Li et al 2020b ), similarly to yeast selenium used as diet supplement (Li et al 2020c ). Also quercetin, a natural flavanol, stimulates translocation of Nrf2 to the nucleus and increases its expression after cell exposure to OTA and thus alleviate the toxicity of this mycotoxin (Ramyaa and Padma 2013 ; Ramyaa et al 2014 ).…”
Section: Natural Antioxidantsmentioning
confidence: 99%